ONLINE TRAINING ON USING VIDEODROIDS AND SMARTPHONES TO INCREASE MOTIVATION OF SAUYUNAN WOMEN FARMER'S GROUP - Tita Rosita; Dede Suryaman (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2021)
This study raised the model of online training in the midst of covid 19, which is about using videodroids and smartphones for Sauyunan women farmers group that is currently very necessary by all levels of society in the face of covid 19. Especially for Sauyunan women farmers group to help communication and marketing activities/marketing of agricultural products online and help her daughter's son who is still in school in following online learning in his school in RW 03 Sarijadi Subdistrict Sukasari Bandung. This research was conducted for three months, starting from February to June 2020. This activity aims to motivate, increase the knowledge, skills, and awareness of mothers who belong to the group of women farmers sauyunan garden about the use of videodroids and smartphones. In today's globalization era, the development of science is very rapid. With this science's development, humans have succeeded in creating discoveries that can facilitate human beings in all things. These discoveries are one of them in the field of information and communication technology. Discoveries in information and communication technology can make it easier for people to communicate and find information, such as mobile phones. A mobile phone is a communication and information tool commonly used by everyone and society to sell products online.